Increased VIP levels in peripheral blood outside migraine attacks as a potential biomarker of cranial parasympathetic activation in chronic migraine. (April 2015) - Cernuda-Morollón, Eva; Martínez-Camblor, Pablo; Alvarez, Rocío; Larrosa, Davinia; Ramón, César; Pascual, J
Aim: The aim of this article is to determine vasoactive intestinal peptide (VIP) levels outside migraine attacks in peripheral blood as a potential biomarker for chronic migraine (CM). Methods: Women older than 17 and diagnosed as CM were recruited. Matched healthy women with no headache history and women with episodic migraine (EM) served as control groups, together with a series of patients with episodic cluster headache in a pain-free period. VIP levels were determined in blood samples obtained from the right antecubital vein by ELISA outside a migraine attack, the patients having taken no symptomatic medication the day before. For ethical reasons, preventives were not stopped. Results: We assessed plasma samples from 119 women with CM, 33 healthy women, 51 matched women with EM and 18 patients (16 males) with cluster headache matched for age. VIP levels were significantly increased in CM (165.1 pg/ml) as compared to control healthy women (88.5 pg/ml) and episodic cluster headache patients (101.1 pg/ml). VIP levels in EM (134.9 pg/ml) were significantly higher compared to controls and numerically lower than those of CM. Thresholds of 71.8 and 164.5 pg/ml optimized the sensitivity and specificity to differentiate CM from healthy controls and EM, respectively. Variables such as age, CM duration, the presence of aura, analgesic overuse, depression, fibromyalgia, vascular risk factors, history of triptan consumption or kind of preventive treatment did not significantly influence VIP levels. Conclusion: Increased interictal VIP level measured in peripheral blood could be a biomarker helping in CM diagnosis, though it does not clearly differentiate between EM and CM.